PERAN SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI SEKOLAH DASAR - Refiana Hidayah; Anam Sutopo; Sofyan Anif (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Teachers’ pedagogical competence plays a central role in ensuring the quality of learning in elementary schools. One strategic effort to support the development of this competence is academic supervision conducted by school principals. This study aims to explore the role of principals’ academic supervision in enhancing teachers’ pedagogical competence at the elementary school level. A qualitative descriptive approach was employed in this research. The participants consisted of a school principal and elementary school teachers selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that academic supervision implemented in a planned and collaborative manner contributes to the improvement of teachers’ pedagogical competence, particularly in lesson planning, instructional implementation, and classroom management. In addition, the supervision process encourages teachers to engage in reflective practices and continuous professional improvement. However, the effectiveness of academic supervision has not been fully optimized due to time constraints and administrative workload, which limit the consistency of follow-up actions. Therefore, academic supervision needs to be designed based on teachers’ actual needs and supported by systematic and continuous follow-up to ensure sustainable improvement in pedagogical competence. ABSTRAKKompetensi pedagogik guru merupakan salah satu faktor utama yang menentukan kualitas pembelajaran di sekolah dasar. Upaya peningkatan kompetensi tersebut dapat dilakukan melalui supervisi akademik yang dilaksanakan oleh kepala sekolah secara terencana dan berkelanjutan. Penelitian ini bertujuan untuk mengkaji peran supervisi akademik kepala sekolah dalam meningkatkan kompetensi pedagogik guru di sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif. Subjek penelitian meliputi kepala sekolah dan guru yang dipilih secara purposive. Pengumpulan data dilakukan melalui wawancara mendalam, observasi pembelajaran, dan dokumentasi. Data dianalisis dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa supervisi akademik yang dilaksanakan secara kolaboratif berkontribusi positif terhadap peningkatan kompetensi pedagogik guru, khususnya dalam perencanaan pembelajaran, pelaksanaan pembelajaran, dan pengelolaan kelas. Supervisi juga mendorong guru untuk lebih reflektif dan terbuka terhadap perbaikan praktik pembelajaran. Namun demikian, pelaksanaan tindak lanjut supervisi belum dilakukan secara optimal karena keterbatasan waktu dan beban administrasi. Oleh karena itu, supervisi akademik perlu dirancang berbasis kebutuhan guru dan didukung dengan tindak lanjut yang sistematis agar peningkatan kompetensi pedagogik dapat berlangsung secara berkelanjutan.